The Roosevelts an intimate history - Ward, Geoffrey C.; Burns, Ken 1953- (Alfred A. Knopf, 2014)
An extraordinarily vivid and personal portrait of America's greatest political family and its enormous impact on our nation--the tie-in volume to the PBS documentary to air in the fall of 2014